PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PADA CV. BANGUN MANDIRI TRUSS - Muhammad Bilal Yassar; Farid Rofif Mukhtar Fauzi; Anto Ashari; Ade Solahudin (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
The purpose of this research is to study how transformational leadership style and organizational culture impact employee performance at CV. Bangun Mandiri Truss. This research uses a quantitative method involving 65 respondents. The data was analyzed through Multiple Linear Regression Analysis using SPSS 29 software. The results of the study indicate that transformational leadership style and organizational culture influence employee performance at CV. Bangun Mandiri Truss by 88.9%. Other variables not examined in this study account for 10.1% of the total influence.